The association between use of antidepressants and bone quality using quantitative heel ultrasound. (May 2015) - Rauma, Päivi H; Pasco, Julie A; Berk, Michael; Stuart, Amanda L; Koivumaa-Honkanen, Heli; Honkanen, Risto J; Hodge, Jason M; Williams, Lana J
Objective: Osteoporosis and depression are major public health problems worldwide. Studies have reported an association between antidepressant use, mainly selective serotonin reuptake inhibitors (SSRIs), and bone mineral density (BMD), but the issue remains unclear. Methods: This study examined data collected from 849 Australian men (aged 24–98 years) participating in the Geelong Osteoporosis Study (GOS). Bone quality was determined using quantitative ultrasound (QUS) and included the following parameters: Broadband Ultrasound Attenuation (BUA), Speed of Sound (SOS) and Stiffness Index (SI). Anthropometry, socio-economic status (SES), medication use and lifestyle factors were determined. The cross-sectional associations between bone quality and use of antidepressants were studied using multivariate linear regression adjusted for potential confounders. Results: At the time of assessment, 61 (7.2%) men were using antidepressants, of which 44 (72.1%) used SSRIs. Antidepressant use was associated with lower SI ( p = .002), SOS ( p = .010) and BUA ( p = .053). However, body weight was identified as an effect modifier; QUS values were lower for antidepressant users with lower weight (< 90 kg) only. Conclusions: Use of antidepressants was associated with lower QUS values for men with low body weights. Thus, the risk of osteoporosis should be taken into account when prescribing antidepressants, in particular among men who are in this weight category.